REFLEKSI RUPA JIWA - Mila Rosinta Totoatmojo (Joged, 2013)
In the era of a fast technological and communication’s advancement, people feels that the worldincreasingly narrowed, as if there is no limit of space and time. The awareness squeezed by everything isgetting closer, and led to act promptly, quickly, and instant. The world seems like a folded or compressed.Man forcing himself to do something with the minimizing quality. What it does have a profound loss ofmeaning. Man is losing his roles as personal (self-reflection) and social (social reflection).The creation of the dance is set from fashion’s manner of self reflection in a front of mirror.In the stepsof process creation of this workbased on Creativity and Choreography. Creativity approach is used in thecreation of art can not be separated from the process of thinking and working creatively, through this way ofthinking and approach a creative work will be built.The second approach is the choreography, which is usedas the foundation in aspects of behavior and other visuals.Artworks " Refleksi Rupa Jiwa /The Reflection Face of Soul" is an exploration of the human psycheneeds to fullfil its personal and social aspects. Its actualization is the result of self-reflection upon thepersonal need as well as social, ie as a dialectic results on both. Corresponding with Sigmund Freud whichis differentiate the human psyche in the id, ego, and super ego, then by self-reflection human will discoverhis/her true identity in fullfil the basic needs of self-satisfaction and lust. In a reflection of social life, peopleare faced with the reality of such as: social relations, ethics, norms, and religion, which sometimes felt as animpediment to fullfil a personal satisfaction and lust. Balance between a self-fulfillment to a fulfilling ofpublic needs on social scope will produce a moral value, in concept of super ego so-called conscience.Key words: self-reflection, social reflection, moral value.